Secretomes of Primary Cancer-associated Fibroblasts Upregulate the Expression of Stemness Markers in HT-29 Human Colorectal Carcinoma Cells - Septelia Inawati Wanandi; Dwi Retna Lestari; Noza Hilbertina; Nurjati Chairani Siregar; Sri Widia Jusman; Murdani Abdullah (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Cancer-associated fibroblast (CAF) is the most abundant tumor stroma. Our previous study has demonstrated that the secretomes of CAF isolated from colorectal carcinoma (CRC) patients could induce epithelial-mesenchymal transition in the HT-29 CRC cell line. However, the role of CAF secretomes in CRC stemness is needed to be further investigated. Therefore, the present study aimed to investigate the effect of CAF secretomes from CRC patients on the expression of stemness markers in HT-29 CRC cells in comparison with the secretomes from normal fibroblasts.METHODS: Fibroblasts were isolated from tumor (CAF) and their counterpart non-tumor (NF) areas of three CRC patients undergone surgical resection. Normal preputium fibroblasts (PF) were isolated during circumcision of three healthy boys aged 8 years. All fibroblasts were grown in free-serum culture medium for 24 hours to collect 50% (v/v) conditioned medium (CM). Then, CM was supplemented to HT-29 CRC cells for 72 hours. The effects of CAF- and NF-CM on the mRNA expression of CD44, CD133, OCT4, and ALDH1A1 were analysed using qRT-PCR. Cells proliferation was measured using the trypan blue exclusion assay.RESULTS: Supplementation of CAF-CM (50% v/v) significantly increased CD44, CD133, OCT4, and ALDH1A1 mRNA expressions compared to that of NF-CM and control without supplementation but had no effect on the proliferation of HT-29 cells.CONCLUSION: CAF secretomes from CRC patients upregulate the expression of CRC stemness.KEYWORDS: cancer-associated fibroblasts, ALDH1A1, OCT4, CD44, CD133, colorectal carcinoma